Kid lawyer eaudiobook - Grisham, John (Theodore Boone, 2010)
The thrilling young mystery series from internationally bestselling author John Grisham! In the small city of Strattenburg, there are many lawyers, and though he’s only thirteen years old, Theo Boone thinks he’s one of them. Theo knows every judge, policeman, court clerk—and a lot about the law. He dreams of being a great trial lawyer, of a life in the courtroom. But Theo finds himself in court much sooner than expected. Because he knows so much—maybe too much—he is suddenly dragged into the middle of a sensational murder trial. A cold-blooded killer is about to go free, and only Theo knows the truth. The stakes are high, but Theo won’t stop until justice is served.